Exogenous IL-9 Ameliorates Experimental Autoimmune Myasthenia Gravis Symptoms in Rats. (3rd October 2018) - Yao, Xiuhua; Zhao, Jiarui; Kong, Qingfei; Xie, Xiaoli; Wang, Jinghua; Sun, Bo; Xu, Lixia; Mu, Lili; Li, Hulun
ABSTRACT: Interleukin-9 (IL-9) is a multifunctional cytokine involved in protective immunity or immunopathology depending on the microenvironment and specific disease settings. Our early study determined that IL-9 and Th9 cells participate in and promote the progression of experimental autoimmune myasthenia gravis (EAMG). The data from this study showed that exogenous recombinant rat IL-9 (rrIL-9) acted as an IL-9 receptor antagonist, reduced the incidence of EAMG in rats, alleviated the severity of the disease, and reduced the anti-acetylcholine receptor (AChR) IgG antibody levels by altering the Th-subset distribution. These data suggest that administration of rrIL-9 may provide a novel therapeutic strategy against MG or related autoimmune diseases. Abbreviations : 2-Mercaptoethanol (2-ME); antibodies (Abs); ?-bungarotoxin (?-BTX); acetylcholine receptor (AChR); airway hyper-reactivity (AHR); allophycocyanin-conjugated (APC); antigen presenting cells (APCs); complete Freund's adjuvant (CFA); Cyanine dye 3 (Cy3); dendritic cells (DCs); experimental autoimmune encephalomyelitis (EAE); experimental autoimmune myasthenia gravis (EAMG); flow cytometry (FACS); fetal bovine serum (FBS); fetal calf serum (FCS); Fluorescein isothiocyanate (FITC); gamma chain (?c); intraperitoneally (i.p.); Incomplete Freund's adjuvant (IFA); interferon (IFN); immunoglobulin (Ig); Interleukin (IL); Janus kinase (JAK); myasthenia gravis (MG); Mononuclear cells (MNC); neuromuscular junctions (NMJ); optical density (OD); ovalbumin (OVA); phosphate-buffered saline (PBS); phycoerythrin (PE); Peridinin chlorophyll protein complex (Percp); Rat AChR ? subunit (R-AChR97-116); Recombinant Rat (rr); room temperature (RT); signal transducer and activator of transcription (STAT); T helper cells (Th).